The optimization of squeeze casting process parameter for AA2219 alloy by using the Taguchi method. (2020) - Karthik, A.; Karunanithi, R.; Srinivasan, S.A.; Prashanth, M.
Abstract: The squeeze casting process have huge potential to produce excellent smooth surface finish profile and have a capability to produce near net product. The squeeze casting is a combination process of forming and forging with a single stage operation without porosity. An attempt is made to optimize the process variables of squeeze casting parameter such squeeze pressure load, die and melt temperature using the L9 orthogonal array with three different levels in order to determine the S/N ratio for density and hardness which is considered as response of the squeeze casting operation. Taguchi analysis performed on the response of squeeze casting in order to determine the most significant process parameter effecting on hardness and density. The Regression equation was devolved to perform a confirmatory test. The Squeeze casting process parameter optimized for AA2219 alloy at squeeze pressure 650 MPa, die pre heating temperature 225°c and melt temperature 700°C which produced better mechanical response and metallography structure. The microstructure of squeeze casted sample was analysed along the radial direction with help of an optical microscope. Microstructure evaluation conforms the presence of fine grains which can be obtained only at the optimized process parameter.